2017
DOI: 10.3329/ajmbr.v2i4.30993
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterization and assessment of genetic parameters of NERICA mutant rice lines under rainfed condition

Abstract: , 100-seed weight (g) and yield plant -1 (g).N 1 /300/P-9-5 had maximum yield plant -1 and N 4 parent had minimum yield plant -1 . All the parental lines showed less yield compared to other mutant lines. The phenotypic coefficient of variations (PCV) were higher than genotypic co-efficient of variations (GCV) for all the traits studied indicating that they all interacted with the environment to some extent. All the traits studied expressed moderate to high heritability estimates ranging from 43.68 to 92.87%. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…In our study, yield per plant, unfilled grains per panicle, number of total tiller, number of effective tiller showed high heritability and genetic advance as percent of the mean value. Similar result in the study of NERICA mutant lines was also observed by [34,31]. On the other hand, [41] found high heritability and genetic advance as percent of the mean value for yield per plant and [42] found high heritability and genetic advance as percent of the mean value for unfilled grains per panicle.…”
Section: Genetic Parameters Of Morphological Traitssupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, yield per plant, unfilled grains per panicle, number of total tiller, number of effective tiller showed high heritability and genetic advance as percent of the mean value. Similar result in the study of NERICA mutant lines was also observed by [34,31]. On the other hand, [41] found high heritability and genetic advance as percent of the mean value for yield per plant and [42] found high heritability and genetic advance as percent of the mean value for unfilled grains per panicle.…”
Section: Genetic Parameters Of Morphological Traitssupporting
confidence: 85%
“…During drought stress fertile tiller number induce approximate 86% of yield changes and hence it is a vital yield attributing character [33]. Moreover, panicle length is also considered an important character as higher panicle length could provide higher grain number [34]. The highest panicle length (29.6 cm) was found in N10/300/P-2-3-5-2 and the lowest (21.6 cm) in N10/300/P-2-3-5-1 mutant genotype with an average of 25.89 ±0.473.…”
Section: Phenotypic Performances Of Mutant Nerica Genotypes Based On mentioning
confidence: 99%